The new chamber building of Malta: architectural image and building technology - Sapienza, Vincenzo (TECHNE - Journal of Technology for Architecture and Environment, 2014)
The knowledge of the most innovative technologies is a basic tool for all the protagonists of the building process. This is because the right resolution of the details is the main way to obtain an architectonic image that is correctly related to the design intents. This work would like to contribute to the spread of the expertise, through the choice of an interesting case study: the new Chamber Building of the Republic of Malta. The history of construction has in the evolution of the stone technology one of the most complex and interesting matter, since the Roman age. The last chapter is probably written in the new Chamber Building of the Republic of Malta, that is going to be finished in the next few months. The concept of the stone façade is founded on two main points, the formal image and the functionality. The article is addressed to the designers, construction managers and researchers who would like to have an approach to the most innovative building technologies.